Estradiol Replacement at the Critical Period Protects Hippocampal Neural Stem Cells to Improve Cognition in APP/PS1 Mice - Qin, Yaoyao; An, Dong; Xu, Weixing; Qi, Xiuting; Wang, Xiaoli; Chen, Ling; Chen, Lei; Sha, Sha (Frontiers in Aging Neuroscience, 2020)
It has been suggested that there is a critical window for estrogen replacement therapy in postmenopausal women with Alzheimer's disease; however, supporting evidence is lacking. To address this issue, we investigated the effective period for estradiol (E2) treatment using a mouse model of AD. Four-month-old female APPswe/PSEN1dE9 (APP/PS1) mice were ovariectomized (OVX) and treated with E2 for 2 months starting at the age of 4 months (early period), 6 months (mid period), or 8 months (late period). We then evaluated hippocampal neurogenesis, β-amyloid (Aβ) accumulation, telomerase activity, and hippocampal-dependent behavior. Compared to age-matched wild type mice, APP/PS1 mice with intact ovaries showed increased proliferation of hippocampal neural stem cells (NSCs) at 8 months of age and decreased proliferation of NSCs at 10 months of age; meanwhile, Aβ accumulation progressively increased with age, paralleling the reduced survival of immature neurons. OVX-induced depletion of E2 in APP/PS1 mice resulted in elevated Aβ levels accompanied by elevated p75 neurotrophin receptor (p75NTR) expression and increased NSC proliferation at 6 months of age, which subsequently declined; accelerated reduction of immature neurons starting from 6 months of age, and reduced telomerase activity and worsened memory performance at 10 months of age. Treatment with E2 in the early period post-OVX, rather than in the mid or late period, abrogated these effects, and p75NTR inhibition reduced the overproliferation of NSCs in 6-month-old OVX-APP/PS1 mice. Thus, E2 deficiency in young APP/PS1 mice exacerbates cognitive deficits and depletes the hippocampal NSC pool in later life; this can be alleviated by E2 treatment in the early period following OVX, which prevents Aβ/p75NTR-induced NSC overproliferation and preserves telomerase activity.